Phyllanthus chapadensis, a new phyllocladiferous Phyllanthus (Phyllanthaceae) from the Chapada dos Veadeiros, Goiás, Brazil - Orlandini, Priscila; Cordeiro, Inês; Da Silva, Marcos José; Castro Souza, Vinicius (Phytotaxa, 2022)
We describe Phyllanthus chapadensis, a new phyllocladiferous species of the genus Phyllanthus probable endemic to the Chapada dos Veadeiros region, Goiás, Brazil, in the Cerrado region. This region is located in Central Brazil with a high number of endemic Angiosperms, unique landscapes, and distinct and peculiar phytophysiognomies. The species described here belongs to Phyllanthus sect. Choretropsis, a Brazilian exclusive group of plants characterized by presenting phylloclades. The new species resembles P. spartioides and P. sarothamnoides, which occur in the Chapada Diamantina, Bahia, Northeastern Brazil, due to its upright shrubby habit, with thin and delicate phylloclades. However, it can be differentiated by the morphological characteristics of phylloclades and flowers. We present the main morphological distinctions between these species, distribution map, illustrations, flowering and fruiting seasons, and a proposal of the conservation status of the new species.